1988
DOI: 10.1295/polymj.20.577
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Transport in Poly(ethylene oxide) (PEO)-LiX Polymeric Solid Electrolyte

Abstract: ABSTRACT:The ionic conductivity behavior of poly(ethylene oxide) complexed with lithium salts was investigated using an a.c. impedance technique. The composition range of the salt was from 0.01 to 0.5 mole fraction. The result showed that anions strongly influence the conductivity behavior of the polymer electrolyte. A simple model is proposed whereby the conductivity decrease at higher salt concentration is due to ion-pair formation. This results in an increase in the activation energy with increasing salt co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…The local relaxation and segmental motion of PEO host are needed for efficient lithium ion transport in the polymer electrolyte, and ionic mobility occurs predominantly in the amorphous phase of PEO. 79,85,90,94,99,122 The perfluoroalkyl sulfonic-type conducting salts like lithium trifluoromethanesulfonate (LiTf), 38,79,99,102,103,109,110,116,[123][124][125][126][127][128][129] lithium bis(trifluoromethanesulfonimidate) (LiTFSI), 103,110,123,[130][131][132][133][134][135] lithium bis(trifluoromethanesulfonimide) (LiBETI), 103,[136][137][138][139][140][141][142] and lithium bis(fluorosulfonyl)amide (LiFSI) 143,144 have high solubility, high ionic conductivity, and high electrochemical stability. These lithium salts with large anions have attracted much attention.…”
Section: Salt-in-polymermentioning
confidence: 99%
“…The local relaxation and segmental motion of PEO host are needed for efficient lithium ion transport in the polymer electrolyte, and ionic mobility occurs predominantly in the amorphous phase of PEO. 79,85,90,94,99,122 The perfluoroalkyl sulfonic-type conducting salts like lithium trifluoromethanesulfonate (LiTf), 38,79,99,102,103,109,110,116,[123][124][125][126][127][128][129] lithium bis(trifluoromethanesulfonimidate) (LiTFSI), 103,110,123,[130][131][132][133][134][135] lithium bis(trifluoromethanesulfonimide) (LiBETI), 103,[136][137][138][139][140][141][142] and lithium bis(fluorosulfonyl)amide (LiFSI) 143,144 have high solubility, high ionic conductivity, and high electrochemical stability. These lithium salts with large anions have attracted much attention.…”
Section: Salt-in-polymermentioning
confidence: 99%
“…8 The salts under study were LiCF 3 SO 3 , LiAIC1 4 , LiAsF 6 , LiBF 4 , and LiPF 6 and the PEO-LiX concentrations were 50:1, 25:1, 8:1, 4:1, 2:1, and 1:1. All subsequent handling of the films and cell manipulation were carried out in the glove-box.…”
Section: Experiments Almentioning
confidence: 98%
“…In a previous study, 8 it was found that the ionic conductivity of the PEO-LiX system was strongly influenced by the salt concentration and anion type. A model was proposed whereby the decrease in the ionic conductivity with increasing salt concentration was due to ion-pair formation.…”
mentioning
confidence: 95%
“…More specifically, a lamellar structure is generally favored for a more symmetrical composition in segregated systems, but it is not possible to ascertain that this type of structure, observed in the case of NaI only, is actually correlated with the maximum volume fraction of the salt in the various blends. On the other hand, the development of longrange order and of a given type of structure may probably depend on more subtle parameters than the overall composition of the system such as the intrinsic properties of the ionic species (shape, size, polarizability [32][33][34][35], trend towards ion-pairing). Here again rationalization of the experimental results remains difficult, as shown by the following examples.…”
Section: Polyzwitterionic Blends With Alkali Metal Saltsmentioning
confidence: 99%
“…Antiplasticization effects are observed in all the other cases, but to highly varying degrees and they are barely significant for trifluoromethanesulfonate, boron tetrafluoride and thiocyanate (⌬T g ≤ 5°C). The size and the polarizability of the anion [32][33][34][35] may contribute in a complex way to the blend behaviors.…”
Section: Polyzwitterionic Blends With Alkali Metal Saltsmentioning
confidence: 99%